Student Deductive Reasoning in Solving Problems of One-Variable Linear Equations Through Problem-Based Learning - Musdin Musdin; Sarfa Wassahua (Lembaga Intelektual Muda (LIM) Maluku, 2021)
Learning is a two-way communication process, and teaching by the teacher as an educator while learning is done by learners or students. Mathematics learning conducted by teachers places less emphasis on aspects of student thinking. Especially using reason in solving various problems faced by students in the learning process. Teachers in learning only focus on the aspect of grades, namely good learning outcomes must be achieved by students. The purpose of this research is to find out the reasoning ability of students on the subject of the one-variable linear equation system through problem-based learning of class VII of SMP Negeri 11 Seram Barat. The type of research used is qualitative descriptive, which is research that aims to obtain data and describe students' deductive reasoning skills on the subject of the one-variable linear equation system through problem-based learning of class VII of SMP Negeri 11 Seram Barat. The number of subjects in this study amounted to 1 person. The instruments used are tests and interviews. The data analysis technique used is qualitative descriptive. Based on the results of the data analysis obtained that the reasoning ability of the subject of class VII SMP Negeri 11 Seram Barat on the material of the linear equation system of one variable obtained the tendency of the subject to have reasoning ability. This is known by the way the problem is used by the subject which starts from general things that have been known the truth and then obtains a more specific conclusion. The subject in his learning has three reasoning indicators used in this study, submitting allegations based on the way the problem is solved by the subject, the subject can give reasons for the arguments presented at the conclusion of the problem in the interview process, and the subject can check the validity of an argument based on the resolution of the problem